ANALISIS DETERMINAN MAKRO EKONOMI TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA PERIODE TAHUN 1990-2021 - Novyanti Tambunan, - (2022)
Economic growth is the process of increasing per capita output over a long period of time. Increased production of services or goods as well as economic activities are associated with economic growth. The research is motivated by the importance of economic growth in Indonesia which is influenced by net exports, the rupiah exchange rate, interest rates, inflation and unemployment on economic growth in Indonesia. This study aims to clarify the effect of net exports, the rupiah exchange rate, interest rate, inflation and unemployment. The sampling method used is purposive sampling, the sample used from 1990 to 2021 consists of 32 data. This study uses quantitative analysis using econometric tool at Eviews 10 using the Error Correction Model (ECM) using time series data. The data collection was taken from the publication of the Central Statistics Agency (BPS), the World Bank, Bank Indonesia and the Digital LAB for Economics UPNVJ. The result of the study show that, (1) Net Export have a negative and significant effect in the long and short term on Indonesia's economic growth, (2) The Rupiah Exchange Rate has a negative and significant effect in the log and short term on Indonesia's economics growth, (3) Interest rate has no effect on Indonesia's economic growth in the log and short them, (4) Inflation has a negative and significant effect on Indonesia's economic growth, (5) Unemployment has a positive effect in the long term but has no effect in the short term on Indonesia's economic growt.